Urban sustainability and Malaysian laws on environmental management of chemical substances - Razman, Muhammad Rizal; Azlan, Azrina; Md Jahi, Jamaluddin; Arifin, Kadir; Aiyub, Kadaruddin; Awang, Zahan; Mohamad, Lukman @ Zawawi (Medwell Journals, 2010)
Agenda 21 based on parts 19.1 and 19.11 highlighted that there are thousands of chemical substances in the world market, a lot of which emerge as poison and toxin in business goods, food and the variety of environmental medium especially in urban area. This has shown that chemical substances bestow awful impact to the environment which includes urban area. Therefore, this study will classify the relevant Malaysian laws on environmental management that managed chemical substances particularly in urban area in order to achieve urban sustainability. This study also has become aware of that there is no specific law in Malaysia that governed the environmental management on chemical substances. However, there are several laws that regulate the environmental management of chemical substances in different area such as the Environmental Quality Act 1974. The Environmental Quality Act, 1974 is related to the control of chemical substances in air and hazardous wastes whilst the Food Act, 1983 controlling chemical substances in the products and goods in the food industry. As for the Occupational Safety and Health Act, 1994 is on regards chemical substances in the occupational environment and meanwhile the Pesticides Act, 1974 to control chemical substances in pesticides. Meanwhile the management of these laws is not the responsible of a single government ministry. Different government ministries may enforce the laws relevant to the operation of that ministry. Hence, the Environmental Quality Act, 1974 is the responsible of the Ministry of Natural Resources and Environment, the Occupational Safety and Health Act, 1994 is by the Ministry of Human Resources whilst the Food Act, 1983 is by the Ministry of Health and as for the Pesticides Act, 1974 under the supervision and administration of the Ministry of Agriculture and Agro-based Industry. Finally this study has concluded that Malaysia has a sufficient laws in which may adequately control chemical substances in various life cycles as to comply with international law particularly in urban area in order to achieve urban sustainability.